Enhancing the understanding of fragmentation processes in hadrontherapy and radioprotection in space with the FOOT experiment. (6th August 2021) - Colombi, S; Alexandrov, A; Alpat, B; Ambrosi, G; Argir, S; Arteche Diaz, R; Bartosik, N; Battistoni, G; Belcari, N; Bellinzona, E; Biondi, S; Bisogni, M G; et al.
Abstract: During proton and carbon ions cancer treatment, nuclear interactions of the beam nuclei with the patient tissues always occur: the former leads to target fragmentation only, the latter to both projectile and target fragments production. In proton therapy the low-energy, high-charge and therefore short-range fragments produced along the beam path in the target fragmentation process may have higher biological effectiveness compared to protons, resulting in a not negligible effect on the delivered dose in a region before the tumor site. In carbon treatments the long range of projectile fragments results in a dose deposition in the healthy tissues behind the tumor site. Therefore, precise fragmentation cross section data would be of great importance to further optimize treatments. At the same time, such data would help improving the design of the shielding of spaceships, especially in view of long distance travels (i.e. Mars human exploration). In fact, nuclear fragmentation occurring between the space background radiation and spacecrafts materials changes the composition of the radiation field and thus the dose received by the astronauts. The FOOT (FragmentatiOn Of Target) experiment has been designed to investigate nuclear fragmentation processes of interest for particle therapy and space radiation protection with a precision in the cross section measurements around 5%. In this work the physics motivations of FOOT and the final design of the experiment will be presented. A performances study of the electronic setup based on FLUKA Monte Carlo simulations and a preliminary analysis of experimental data are reported as well.